DIGITAL TRANSFORMATION CAPABILITY AND MSME RESILIENCE:AN INTEGRATIVE FRAMEWORK FOR SUSTAINABLE BUSINESS ADAPTATION - Anggun Yolistina; Nida Garnida Fitrianti (Journal of Jabar Economic Society Networking Forum, 2024)
Background: Digital transformation has become an important pathway through which micro, small, and medium enterprises (MSMEs) improve market access, operational visibility, customer interaction, and organizational flexibility. Yet technology adoption alone does not guarantee resilience. The value of digitalization depends on managerial capability, organizational learning, resource orchestration, cybersecurity awareness, and the ability to integrate digital tools with business processes. Aims: This article develops an integrative framework explaining how digital transformation capability can contribute to MSME resilience and sustainable business adaptation. Research Method: The study uses an integrative conceptual review of literature on digital transformation, dynamic capabilities, organizational resilience, digital entrepreneurship, and SME adaptation. It presents no fabricated survey, interview, experimental, or statistical data. Results and Conclusion: The synthesis suggests that resilient digital transformation requires five connected capabilities: digital sensing, selective technology adoption, process integration, data-informed decision making, and adaptive reconfiguration. Digital tools strengthen resilience when they diversify market channels, improve information quality, reduce critical dependencies, and accelerate organizational learning. Unmanaged digital dependence may instead create platform, cybersecurity, financial, and capability risks. Contribution: The paper proposes a Digital Transformation-to-Resilience Framework and a practical capability matrix for future empirical testing and MSME development programs.